High expression of VTA1 is an adverse prognostic factor in lung adenocarcinoma: High expression of VTA1 affects prognosis of lung adenocarcinoma - Sun, Xingang; Wu, Ruixin; Guan, Xinjun; Dong, Changsheng; Qiu, Dongze; Xia, Guojie; Feng, Shouhan; Duan, Jinlong; Zhang, Lei (Cellular and Molecular Biology, 2024)
Lung adenocarcinoma (LUAD) is a common pathological type of non-small cell lung cancer; identifying preferable biomarkers has become one of the current challenges. Given that VTA1 has been reported associated with tumor progression in various human solid cancers but rarely reported in LUAD, herein, RNA sequencing data from TCGA and GTEx were obtained for analysis of VTA1 expression and differentially expressed gene (DEG). Furthermore, functional enrichment analysis of VTA1-related DEGs was performed by GO/KEGG, GSEA, immune cell infiltration analysis, and protein-protein interaction (PPI) network. In addition, the clinical significance of VTA1 in LUAD was figured out by Kaplan-Meier Cox regression and prognostic nomogram model. R package was used to analyze incorporated studies. As a result, VTA1 was highly expressed in various malignancies, including LUAD, compared with normal samples. Moreover, high expression of VTA1 was associated with poor prognosis in 533 LUAD samples, as well as T stage T2&T3&T4, N stage N1&N2&N3, M stage M1, pathologic stage II&III&IV, and residual tumor R1&R2, et al. (P < 0.05). High VTA1 was an independent prognostic factor in Cox regression analysis; Age and cytogenetics risk were included in the nomogram prognostic model. Furthermore, a total of 4232 DEGs were identified between the high- and the low-expression group, of which 736 genes were up-regulated and 3496 genes were down-regulated. Collectively, high expression of VTA1 is a potential biomarker for adverse outcomes in LUAD. The DEGs and pathways recognized in the study provide a preliminary grasp of the underlying molecular mechanisms of LUAD carcinogenesis and progression.